Permaianan Tradisonal Budaya Martumba Sebagai Media Pendidikan Karakter Bagi Anak di Batak Toba - Friska Aritonang; Iky Sumarthita Putri Prayitno; Yurulina Gulo (Universitas Negeri Medan, 2020)
This paper aims to determine the effect of traditional Martumba games on children's character education. Martumba is a traditional game while dancing. Martumba was originally performed at night in page during the poltak of the moon, this dance is played adults, where men insinuate each other describing the introduction of the Toba Batak youth in ancient times to the woman he liked. But along with times, this game is no longer done at night but in accordance with the context of the activity and the players are no longer adults but children and adolescents. Given that children are the right media in maintaining the culture of the modern era. This paper uses a qualitative research method with a qualitative descriptive approach to children in Batak Toba through cultural memory theory and this study concludes that the Martumba Traditional game has an influence on children's character development because the game can be used as a teaching medium for children because in it there are activities to educate characters children who are disciplined, communicative, cooperate with groups, observations and as a means of interaction between humans so that children's creativity will emerge through movements and interpret songs to the message to be conveyed through song and movement in the game.